Clinical, haematological and biochemical studies in goats naturally infected with Mycoplasma agalactiae - Kizil, Omer; Ozdemir, Haydar (Natl Veterinary Research Inst, 2006)
The aim of this study was to investigate some clinical, haemotological and biochemical parameters in goats with contagious agalactia caused by Mycoplasma agalactiae. Forty seven goats showing clinical signs of contagious agalactia and 20 healthy goats were used in the study. Concentrations of plasma biochemical parameters were analysed by a clinical chemistry analyser, and packed cell volume, haemoglobin concentration, and red blood cell and white blood cell counts were determined using an automatic blood counter. There was positive result in the PCR analysis for Mycolasma agalactiae. The body temperature, pulse and respiration rates, aspartate aminotransferase and lactate dehydrogenase activity in plasma were significantly higher in the infected goats than in the controls, while rumen contractions, plasma total protein, albumin and glucose concentrations were significantly lower. No significant difference relative to white and red blood cell counts, packed cell volume, haemoglobin concentration, alkaline phosphatase and gamma-glutamyl transferase activity, and sodium, potassium and chloride concentrations between the groups were found.
Keywords: goat; Mycoplasma agalactiae; haematology; biochemistry